SWIMMING CRAWL STYLE: THE EFFECT OF PURE OR PROGRESSIVE METHOD AND LEVEL OF BODY FAT - Subagyo Subagyo; Guntur Guntur; Abdul Alim (LPMPP Universitas Negeri Yogyakarta, 2020)
The crawl style is a freestyle which is frequently used in national and international competitions. However, this swimming style requires much attention because of its complexity. On the other hand, it is very beneficial despite the facts that athletes do not like it. The objectives of this research were to examine the significant difference between two teaching methods: the pure and the progressive teaching methods. The sample of this study were 32 male students from a junior high school in Yogyakarta. The sample were divided into two groups with 16 students in the control group and 16 students in the experimental group. The data in this study were collected through a measurement on the students crawl style basic movements and the body fat level. The data were subsequently analyzed with independent sample t-test and correlation by the means of SPSS version 23. The result showed that there was a significant difference of basic movement score between the pure method and progressive method learning with p value of 0.03 0.05. The level of fat was not a constraint on both methods of teaching. High and low fat were positively correlated on both methods with the strength of the correlation was very high. In conclusion progressive method was better method to teach crawl style compared to the pure method of teaching because it gave many benefits for learners compared to the pure method teaching, regardless the level of the body fat.